IMPLEMENTASI KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH MELALUI KETELADANAN DALAM PENGEMBANGAN BUDAYA PRESTASI SISWA (Studi Kasus Di SMAN 1 Puri Kabupaten Mojokerto) - Siti Arofah; Gunarti Dwi Lestari; Ima Widiyanah (STKIP Pesisir Selatan, 2026)
The role of transformational leadership in fostering a culture of student achievement is highly significant and has been practiced at SMA Negeri 1 Puri, Mojokerto Regency. However, existing studies on this topic have predominantly focused on literature reviews, while empirical investigations remain limited. Therefore, this study aims to analyze the role of the principal’s leadership in developing a culture of student achievement using the transformational leadership framework, which comprises the four dimensions known as the Four I’s: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. This study employed a qualitative approach with a case study design. The findings indicate that the principal of SMA Negeri 1 Puri, Mojokerto Regency, has effectively implemented transformational leadership in fostering a culture of achievement. In terms of idealized influence, the principal demonstrated exemplary leadership through academic productivity, literacy promotion, educational innovation, and various professional accomplishments that inspired members of the school community. Regarding inspirational motivation, the principal successfully established a collective vision of a high-achieving school through various flagship programs that encouraged students’ motivation and commitment to achievement. In the dimension of intellectual stimulation, the principal promoted a culture of innovation, creativity, and continuous learning through educational innovations and the strengthening of literacy practices.